Transforming Islamic Education in Modernity: Reassessing Sir Syed Ahmad Khan’s Thought - Muhammad Zidan Nur Ihsan; Mutohharun Jinan; Muh. Nur Rochim Maksum; Muhammad Badat Alauddin (Universitas Al-Amien Prenduan, 2025)
This article analyzes Ahmad Khan's educational thought as part of the epistemological reform project in Islamic education in the 19th-century colonial context. Using a literature review approach, this article explores the social background, philosophical foundations, epistemology, methodological goals, and criticisms and limitations of the educational reform initiated by Khan. The results show that Ahmad Khan's educational thinking cannot be reduced to a form of westernization or a pragmatic response to British colonialism. Khan's thinking is rooted in an internal critique of the intellectual stagnation of Muslims triggered by the dichotomy of knowledge, the dominance of taqlid, and the reduction of education to a means of doctrinal transmission. Through the integration of revelation and reason, Ahmad Khan shifted the conflict between religion and science from the theological realm to the methodological, thus opening space for affirming scientific rationality without discarding the role of revelation as a moral and spiritual orientation. However, this article also emphasizes that Khan's integration remains transitional and problematic, due to the lack of a strict methodological framework for defining the limits of intellectual authority and the social limitations on its implementation. Thus, the main contribution of Khan's educational thought lies in opening the crustacean shell for the development of modern Islamic education, not in the order of the final educational model itself, which is ready to be implemented.